KINERJA PORTOFOLIO SAHAM PADA SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA - Maryam Nadir (AKUNTABEL, 2013)
The performance of stock portfolio observe not only return but also consider the risk of portfolio. There are several methods that can be used to measure the performance of portfolios using index Sharpe and Treynor index. Stock portfolio performance measurement can be facilitated by using a proxy that LQ 45, a liquid stock market capitalization is high, has a high-frequency trading, does not fluctuate and objectively has been selected by the Stock Exchange. The purpose of this research is to analyze the performance of mining stock portfolio using the Sharpe index and Treynor index in Indonesia Stock Exchange. This study tries to analyze the performance of mining stocks listed on the Indonesia Stock Exchange in the period 2011-2012 using the index Sharpe and Treynor index. The results showed that by using the index Sharpe and Treynor index no stock are performing well. All stock is negative. Performance ratings Sharpe index and Treynor index indicates that the stock portfolio ADRO ITMG is ranked one with an index Sharpe value of -0073 and Treynor index values -0.005.Keywords: Sharpe index, Treynor index, Stock, Portfolio Performance, LQ45